2016
DOI: 10.1021/acsami.5b12030
|View full text |Cite
|
Sign up to set email alerts
|

Design of Nanostructured Heterogeneous Solid Ionic Coatings through a Multiscale Defect Model

Abstract: Understanding of the electrical conduction, that is, ionic and electronic conduction, through the solid electrolyte interphase (SEI) is critical to the design of durable lithium-ion batteries (LIBs) with high rate capability and long life. It is believed that an ideal SEI should not only be an ionic conductor, but also an electronic insulator. In this study, we present a theoretical design of an artificial SEI consisting of lithium fluoride (LiF) and lithium carbonate (Li2CO3) on a LIB anode based on a newly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 70 publications
1
53
1
Order By: Relevance
“…38,169,179 Another method to increase the diffusion carrier concentration is taking advantage of the space charge layer effect 184 created by heterogeneous structures and grain boundaries. 34,185 Given the difference of the Li diffusion carriers in Li 2 CO 3 and LiF, Pan et al 185 combined the DFT predicted interfacial defect reaction energetics and the continuum Poisson-Boltzmann relationship to understand the effect of mixing LiF and Li 2 CO 3 on Li-ion conductivity. They found that a space charge layer is formed via the defect reaction across the Li 2 CO 3 and LiF interface, which results in the dramatically increased Li-ion interstitial concentration in Li 2 CO 3 and an increased Li vacancy concentration in LiF, as illustrated in Fig.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
See 1 more Smart Citation
“…38,169,179 Another method to increase the diffusion carrier concentration is taking advantage of the space charge layer effect 184 created by heterogeneous structures and grain boundaries. 34,185 Given the difference of the Li diffusion carriers in Li 2 CO 3 and LiF, Pan et al 185 combined the DFT predicted interfacial defect reaction energetics and the continuum Poisson-Boltzmann relationship to understand the effect of mixing LiF and Li 2 CO 3 on Li-ion conductivity. They found that a space charge layer is formed via the defect reaction across the Li 2 CO 3 and LiF interface, which results in the dramatically increased Li-ion interstitial concentration in Li 2 CO 3 and an increased Li vacancy concentration in LiF, as illustrated in Fig.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
“…34 It would be ideal if the Li 2 CO 3 /LiF interface is perpendicular to the anode surface and the size and distribution of LiF can be controlled experimentally as the model had suggested. 185 This is an important step to describe the mosaic nature of the SEI film.…”
Section: Correlation Of Sei Properties With Battery Performance Starmentioning
confidence: 99%
“…During the past two and half decades, great efforts have been devoted to Lithium-ion batteries (LIBs). [4][5][6][7][8][9][10] However, the limited global availability of lithium resources, safety and high cost of extraction hinder the application of LIBs in several energy storage systems. This demands alternative energy storage devices that are based on earth-abundant elements.…”
mentioning
confidence: 99%
“…We conclude that ionic conductivity of the SEI can be promoted by introducing LiF/Li 2 CO 3 interfaces. Experimentally it has been demonstrated, that LiF/Li 2 CO 3 interfaces as an artificial SEI layer on Si improves the cycling performance …”
Section: Efforts To Enhance the Si Electrode Stabilitymentioning
confidence: 99%